Institutional Barriers to Small Scale Business Development in Jaffna District - Thevaranchany, S.; Subajini, S. (JUICE- 2012 University of Jaffna, 2012)
The present study intended the title “Institutional Barriers to Small scale business development in Jaffna District”. Institutional barriers perform on many levels; from grass-roots contact with possible customers to political, country-specific agendas and these can be constraints inherent in a development program. In Northern Province many infrastructure facilities are now on going. Therefore it is a wonderful opportunity for the youngsters to develop their entrepreneurial activities. Like other war-time and post-war countries such as Lebanon, Tanzania and Nigeria start post war development in country through Small Scale business development. The main objective of this research was to ascertain the conception of Small scale entrepreneurs about obstacles they face while developing their Businesses in Jaffna District There are 113 Small scale businesses in Jaffna District. But the researcher selected the 50 establishments. It represents 44% of the whole population. The researchers used convenience random sampling method to select the small scale entrepreneurs in Jaffna. The structured questionnaire and Interview were used to collect data and it was analyzed by universal analysis, by using SPSS computer package such as regression and correlation. The overall results were found according to the discussion that the institutional barriers which have adversely affected the small scale business development in Jaffna district (sig:0.000) and then this study indicates that awareness (sig:0.001) and competition (sig:0.001) are the most important barriers to small scale business development. So the research objectives are achieved through this survey. In addition to the above, this study offers some suggestion to overcome these barriers.